2015
DOI: 10.1080/01652176.2014.991048
|View full text |Cite
|
Sign up to set email alerts
|

The effect of infection with mixedEimeriaspecies on hematology and immune responses following Newcastle disease and infectious bursal disease booster vaccination in broilers

Abstract: Background: Coccidiosis is an important parasitic disease of chickens, causing high mortality and morbidity. This morbidity is believed to be correlated with altered population dynamics of blood cells and immunocompromisation. Objectives: This study investigated the effects of mixed Eimeria species (viz., tenella, maxima, acervulina and necatrix) infection on hematology and immune responses following Newcastle disease (ND) and infectious bursal disease (IBD) booster vaccination in broilers. Animals and methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(21 citation statements)
references
References 23 publications
5
14
2
Order By: Relevance
“…As the weight of lymphoid organs can be used as an indication of the body’s ability to deliver lymphoid cells during immune responses [40], we evaluated the relative weight of the bursa of Fabricius and of the spleen. We observed that EC broilers showed lower relative weight of the bursa of Fabricius, as reported in other study [41], and higher relative weight of the spleen and whole intestine, which is also in agreement with the results of previous works [42, 43]. A low relative weight of the bursa of Fabricius can be attributed to organ atrophy caused by lymphocyte depletion or to micronecrosis and cell migration [44].…”
Section: Discussionsupporting
confidence: 92%
“…As the weight of lymphoid organs can be used as an indication of the body’s ability to deliver lymphoid cells during immune responses [40], we evaluated the relative weight of the bursa of Fabricius and of the spleen. We observed that EC broilers showed lower relative weight of the bursa of Fabricius, as reported in other study [41], and higher relative weight of the spleen and whole intestine, which is also in agreement with the results of previous works [42, 43]. A low relative weight of the bursa of Fabricius can be attributed to organ atrophy caused by lymphocyte depletion or to micronecrosis and cell migration [44].…”
Section: Discussionsupporting
confidence: 92%
“…[ 35 ] and Akhtar et al . [ 36 ] that infected broilers had higher numbers of leukocytes and differential leukocytes relative to non-infected birds. This increased leukocytes and differential leukocytes were attributed to the induction of immune responses of the infected broilers against infectious agents [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] that infected broilers had higher numbers of leukocytes and differential leukocytes relative to non-infected birds. This increased leukocytes and differential leukocytes were attributed to the induction of immune responses of the infected broilers against infectious agents [ 36 ]. Owing to these earlier data, it may be suggested that supplementation with multistrain probiotics in combination with vitamins and minerals was able to alleviate the potential infections (from the field), resulting in less induction of immune responses of broilers.…”
Section: Discussionmentioning
confidence: 99%
“…An important reason may be poor vaccination technique or incorrect handling of the vaccines (Gallili & Ben-Nathan, 1998;Dortmans et al, 2012). Other factors reported that may impair the immune response are those of concurrent disease or infestation by internal parasites, nutritional problems, other vaccines, high level off maternal antibodies and stress (Eidson et al, 1982;Gallili & Ben-Nathan, 1998;Seal et al, 2000;Akhtar et al, 2015). In this study information on concurrent disease, infestation by internal parasites, nutritional problems and stress were not reliably available.…”
Section: Discussionmentioning
confidence: 79%